THE EFFECT OF COMPENSATION, WORK DISCIPLINE, AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. INFO CEMERLANG ANDAL NUSA - Puspitasari, Desy; Mohamad Trio Febriyantoro; Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
Research this aim for knowing influence compensation, discipline work and motivation to performance employees at PT. Info Cemerlang Andal Nusa Tangerang. Method data collection with To do deployment questionnaire in its entirety employees totaling 40 people, so set as sample fed up or total sample. Data analysis was performed with SPSS Statistics for Windows version 23. The results showed that from the results of the F test that the variables Compensation , Work Discipline and Motivation had a positive and significant effect on employee performance. Research results this show that compensation take effect positive and significant to performance employee. Discipline work take effect negative and significant to performance employee. Motivation take effect positive and significant to performance employee.